PERBANDINGAN EFEKTIFITAS JUS LIDAH BUAYA DAN KLORHEXIDIN 0.06% TERHADAP JUMLAH KOLONI STREPTOCOCCUS MUTANS SALIVA ANAK DENGAN KARIES - Shanty Chairani; Sri W Rais; Rani Purba; Amalia AH (Odonto : Dental Journal, 2018)
Background: Aloe vera contains active components such as antrhaquinones,saponin, glucomannans, and acemannans that have been known for its antimicrobial properties. In vitro study showed that Aloe vera extract can inhibit the growth of Streptococcus mutans. Studies reported that children with caries have high level of salivary S. mutans which is the main pathogen in dental caries. The gold standard mouthrinse for dental caries is chlorhexidine gluconate, but it has several side effects. The objective of this study was to compare the effect between Aloe vera juice and 0.06% chlorhexidine mouth rinse on salivary S. mutans in children with caries.Methods: This experimental research with pretest and post-test control group design conducted on 30 children (6-12 years old) with number of carious teeth >4. Subjects divided into 2 groups: Aloe vera juice group and 0.06% chlorhexidine group, which instructed to rinse their mouth with 10 ml stated mouthwash, twice a day, during 7-day period. Unstimulated saliva was collected at baseline and after 7 days then inoculated on mitis salivarius bacitracin agar. S. mutans were counted and expressed in CFU/ml. Data were analyzed using paired t-test and independent t-test.Result: The result showed that a significant reduction in salivary S.mutanscounts was observed with Aloe vera juice mouth rinse and 0.06% chlorhexidine (p<0.05). The mean reduction of S. mutans counts was not statistically significantly between grup (p>0.05).Conclusion: These findings suggest that Aloe vera juice can reduce salivary S. mutans in children with caries so it can be considered as alternative mouthwash to prevent caries.